Overcoming Universal Restrictions on Metal Selectivity by Protein Design - Choi, Tae Su; Tezcan, F. Akif (Nature (London), 2022)
Selective metal coordination is central to the functions of metalloproteins:1,2 each metalloprotein must pair with its cognate metallocofactor to fulfl its biological role3 . However, achieving metal selectivity solely through a three-dimensional protein structure is a great challenge, because there is a limited set of metal-coordinating amino acid functionalities and proteins are inherently fexible, which impedes steric selection of metals3,4 . Metal-binding afnities of natural proteins are primarily dictated by the electronic properties of metal ions and follow the Irving–Williams series5 (Mn2+ < Fe2+ < Co2+ < Ni2+  Zn2+) with few exceptions6,7 . Accordingly, metalloproteins overwhelmingly bind Cu2+ and Zn2+ in isolation, regardless of the nature of their active sites and their cognate metal ions1,3,8 . This led organisms to evolve complex homeostatic machinery and non-equilibrium strategies to achieve correct metal speciation1,3,8–10. Here we report an artifcial dimeric protein, (AB)2, that thermodynamically overcomes the Irving–Williams restrictions in vitro and in cells, favouring the binding of lower-Irving–Williams transition metals over Cu2+, the most dominant ion in the Irving–Williams series. Counter to the convention in molecular design of achieving specifcity through structural preorganization, (AB)2 was deliberately designed to be fexible. This fexibility enabled (AB)2 to adopt mutually exclusive, metal-dependent conformational states, which led to the discovery of structurally coupled coordination sites that disfavour Cu2+ ions by enforcing an unfavourable coordination geometry. Aside from highlighting fexibility as a valuable element in protein design, our results illustrate design principles for constructing selective metal sequestration agents.